PKM Parenting: Memahami Perkembangan Kognisi Anak - Nurfitriany Fakhri; Irdianti Irdianti; Sahril Buchori (Jurnal Kebajikan: Pengabdian Kepada Masyarakat, 2024)
The development of children's cognition, especially at the early school age, is one of the keys to success in human growth and development. However, parents and teachers may experience limited understanding and skills in identifying, stimulating and evaluating children's cognitive development according to their developmental stage. To overcome partner problems, the PKM implementation team proposed training activities with the ultimate goal of helping parents and teachers at Pertiwi Kindergarten, South Sulawesi, in developing understanding and skills to support the cognitive development of kindergarten-aged children. PKM activities are carried out in the form of parenting seminars, with participants from parents and teachers at Pertiwi Kindergarten, South Sulawesi. Overall, the parenting seminar activity on optimizing the cognitive development of kindergarten age children at Pertiwi Kindergarten, South Sulawesi has been carried out very well and achieved the expected goals. The high level of participation and enthusiasm of participants, reflected in the presence of participants and their active involvement in discussions, shows the success of this program in meeting partners' needs.